A Digital Dakon Game for Elementary Mathematics Learning: An ADDIE-Based Development - Muhammad Aulia Nalendra; Chanifah Indah Ratnasari (Komunitas Dosen Indonesia, 2026)
Mathematics learning in elementary school often relies on repetitive exercises that can reduce student engagement and motivation. Digital game-based learning provides opportunities to create interactive learning environments by integrating instructional content into gameplay. In addition, ethnomathematics emphasizes connecting mathematical concepts with familiar cultural contexts. One traditional Indonesian game with mathematical potential is Dakon, which involves counting, comparison, and distribution activities. This study aimed to develop and evaluate a culturally contextualized digital mathematics game based on Dakon for elementary school students. The study contributes by integrating ethnomathematics into a structured digital game-based learning environment using the ADDIE instructional design model. The game was implemented as an Android-based application using Unity game engine with a rule-based AI opponent. Arithmetic questions were embedded into gameplay across three progressive levels to support gradual learning. The implementation involved twenty third-grade students from MI Fajar Siddiq Elementary School in Palembang, Indonesia. System functionality was validated using black-box testing, while user evaluation was conducted using a 13-item Likert-scale questionnaire measuring usability, attractiveness, effectiveness, and user acceptance. The results showed that all system features functioned as expected. User evaluation indicated positive perceptions with mean scores of 4.19 (usability), 4.17 (attractiveness), 4.38 (effectiveness), and 4.30 (user acceptance), with an overall mean of 4.25 and a feasibility percentage of 85%. The reliability test yielded a Cronbach’s alpha of 0.88, indicating strong internal consistency. These findings suggest that integrating culturally relevant games into digital learning environments can enhance engagement and support mathematics learning.